The knowledge, perception, and acceptability of insects as food among the East Coast Malaysians - Nur Zulaikha Kamaruzaman,; Tan, Yi-Li; Nurul Hanisah Juhari,; Abd Rahim Muhamad Hafiz,; Mohammad Rashedi Ismail-Fitry, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Insects have gained attention as a sustainable protein source, yet entomophagy remains relatively unpopular, particularly in modern societies like Malaysia. This study evaluates the knowledge, acceptability, and perceptions of insect consumption among residents of the East Coast of Malaysia (ECM). A structured survey was administered to 201 respondents, gathering data on socio-demographic factors, knowledge, perceptions, and acceptability of insects as food. Descriptive statistics, cross-tabulation, correlation, and regression analysis were conducted using IBM SPSS Statistical version 26. A majority of respondents (74.6%) demonstrated moderate knowledge about insect consumption; however, 60.7% of respondents held negative perceptions, and 79.6% showed low acceptability, with significant sociodemographic differences by ethnicity, education, income, gender, and age. A positive relationship was found between knowledge, perceptions, and willingness to consume insect-containing foods (ICF), with statistical data confirming knowledge, acceptability, and perception as significant predictors of ICF willingness (P<0.05). The findings highlight the need for public education to improve perceptions and increase consumer acceptance of insects as a viable protein source. Addressing safety and halal compliance concerns is essential to foster greater acceptance. Future research should expand the sample size and data collection period to explore the commercialisation potential of insects as food in Malaysia.